Risk factors for ocular biological parameters in Chinese preschool children: a cohort study from the Beijing whole childhood eye study - Qin, Xi; Sun, Yunyun; Wang, Shana; Xie, Xiaolan; Gao, Lei; Li, Huijian; Wei, Ruihua; Fu, Jing; Zhu, Bidan (Frontiers in Medicine, 2025)
BackgroundThe high myopia prevalence in young East Asian children necessitates early detection and prevention strategies. Axial length (AL), corneal radius of curvature (CR), and the AL to CR ratio (AL/CR) are potential myopia biomarkers. However, the influence of genetic, growth and development, and environmental factors on these metrics in Chinese preschool children remains unclear. Therefore, this study aimed to investigate the effects of these factors on the AL, CR, and AL/CR ratio in children aged 3–6 years in Beijing.MethodsIn this 3-month study, initiated in November 2021, children aged 3–6 years from nine kindergartens in Beijing were randomly selected for ocular biological parameter measurements. The height and weight of each child were measured, and their parents completed a questionnaire on parental myopia and environmental influences. The AL/CR ratio were calculated. One-way analysis of variance, univariate analysis, and multiple linear regression models (with age, sex, height, weight, parental myopia, continuous near-work time, electronic products use, and outdoor activity time as variables) were used to compare the effects of different variables on the AL, CR, and AL/CR ratio.ResultsOverall, 1,353 participants (708 boys; mean age, 4.37 ± 0.82 years) were included in this study. The multiple linear regression analysis revealed that parental myopia significantly increased the AL and AL/CR ratio (p = 0.002, p < 0.001). Male participants had a longer AL, larger CR, and greater AL/CR ratio than female participants (all p < 0.001). A longer AL and larger CR were associated with greater height (both p < 0.001). The AL/CR ratio increased with age (p < 0.001). The CR was positively associated with the amount of time spent outdoors (p = 0.004).ConclusionOcular biological parameters are influenced by genetic, growth and development, and environmental factors. Among children aged 3–6 years in Beijing, monitoring growth and development, investigating parental myopia, and evaluating eye habits have certain guiding significance for delaying increases in the AL and AL/CR ratio. This study may provide some suggestions for the development of healthy eye habits.